Calcule a soma das raizes da equação de 2º grau eo produto da equação
A= 3x²-10x+5=0
B= 3x²-x-5=0
C= 2x²-7=0
D= x(x-3)=2
Respostas
respondido por:
2
A) 3x² - 10x + 5 = 0
Δ = b² - 4ac
Δ = 100 - 60
Δ = 40
x = -b ± √Δ
2a
x = 10 ± 40 --> X1 = 50 = 25
6 6 3
X2 = - 30 = - 5
6
Soma de x1 + x2 = 25 + (-5)
3
= 25 - 5
3
= 25 - 15 --> 10
3 3
B) 3x² - x - 5 = 0
Δ = 1 + 60
Δ = 61
x = 1 ± 61 --> X1 = 62 = 31
6 6 3
X2 = - 60 = - 10
6
Soma de x1 + x2 = 31 - 10
3
= 31 - 10 --> 21
3 3
C) 2x² - 7 = 0
Δ = 0 + 56
Δ = 56
x = ± 56 --> X1 = 56 = 14
4 4
X2 = - 56 = - 14
4
Soma de x1 + x2 = 14 + (-14)
= 14 - 14
= 0
D) x(x - 3) = 2
x² - 3x - 2 = 0
Δ = 9 + 8
Δ = 17
x = 3 ± 17 --> X1 = 20 = 10
2 2
X2 = - 14 = - 7
2
Soma x1 + x2 = 10 + (-7)
= 10 - 7
= 3
Δ = b² - 4ac
Δ = 100 - 60
Δ = 40
x = -b ± √Δ
2a
x = 10 ± 40 --> X1 = 50 = 25
6 6 3
X2 = - 30 = - 5
6
Soma de x1 + x2 = 25 + (-5)
3
= 25 - 5
3
= 25 - 15 --> 10
3 3
B) 3x² - x - 5 = 0
Δ = 1 + 60
Δ = 61
x = 1 ± 61 --> X1 = 62 = 31
6 6 3
X2 = - 60 = - 10
6
Soma de x1 + x2 = 31 - 10
3
= 31 - 10 --> 21
3 3
C) 2x² - 7 = 0
Δ = 0 + 56
Δ = 56
x = ± 56 --> X1 = 56 = 14
4 4
X2 = - 56 = - 14
4
Soma de x1 + x2 = 14 + (-14)
= 14 - 14
= 0
D) x(x - 3) = 2
x² - 3x - 2 = 0
Δ = 9 + 8
Δ = 17
x = 3 ± 17 --> X1 = 20 = 10
2 2
X2 = - 14 = - 7
2
Soma x1 + x2 = 10 + (-7)
= 10 - 7
= 3
dheninha12:
muito obrigada
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás